2022
DOI: 10.7759/cureus.28781
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study on Correlation of First Trimester Crown-Rump Length With Birth Weight

Abstract: BackgroundUltrasound examination has been a crucial part of the evaluation of fetal health during pregnancy. It has become more accurate over the past few decades as a result of advances in radiodiagnostic imaging. While obstetric ultrasonography in the first trimester has been utilized extensively for gestational age assessment and confirmation of fetal viability, the imaging technique has seen little exposure in predicting pregnancy outcomes. This study was thus undertaken to find out any possible associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…The mean age of the females under investigation in our study was determined to be 26.98±4.26, which was in line with the findings of a previous study by Patel et al [6] , which revealed that the study population's mean age was 26.6 years.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of the females under investigation in our study was determined to be 26.98±4.26, which was in line with the findings of a previous study by Patel et al [6] , which revealed that the study population's mean age was 26.6 years.…”
Section: Discussionsupporting
confidence: 92%
“…Thereafter the trend was reversed and the fetuses of white women assumed a longer crown-rump length than those of their black counterpart at a matched gestational age till the end of the first trimester. This was indirectly related to the study done by Kramer et al 37 . It was concluded in their study that the closer coherence of revealed small for gestational age (SGA) and neonatal mortality rates based on a single standard and the intermediate pattern among foreign-born Blacks strongly suggested that Black-White differences in birth weight for gestational age were pathological rather than physiological.…”
Section: Discussionmentioning
confidence: 64%
“…The measurement of fetal crown-rump length (CRL) during early pregnancy ultrasound examinations (11–14 weeks) is crucial for accurate fetal gestational age determination 1 2 , chromosomal abnormality risk assessment 3 4 5 , and fetal growth and development evaluation 6 7 8 . However, inaccuracies in CRL measurements, which are influenced by fetal position, can significantly impact clinical decision-making and potentially lead to adverse pregnancy outcomes 9 .…”
Section: Introductionmentioning
confidence: 99%